Cobalt chloride exposure disturbs spindle assembly and decreases mouse oocyte development potential. (1st March 2023) - Zhao, Si-Cheng; Qiao, Feng-Xin; Sun, Ming-Xin; Liu, Yue-Cen; Wang, Hai-Long; Xu, Zhi-Ran; Liu, Yu
Abstract: Cobalt is a kind of heavy metal which is widely used in petrochemical and biomedical industries. Animal studies have reported that cobalt would exert systemic toxicity, but its effects on the ovarian function in mammals, especially for oocyte quality remains unknown. In the present study, we report that cobalt chloride treatment affects ovary coefficient and follicular growth. Oocytes in cobalt chloride exposed mice exhibited a decreased development potential, with the evidence of decreased occurrence rate of germ vesicle breakdown and polar body extrusion. Besides, cobalt chloride disorganized meiotic spindle formation and movement, mechanically associated with affecting TACC3 and Ac-a-tubulin levels, and disturbing actin reorganization. In addition, cobalt chloride exposure result in mitochondrial cristae structures disappear, cluster distribution and potential depolarization. Altogether, these findings suggest that cobalt chloride impairs the ovarian follicle growth and affects oocyte development by disrupted spindle assembly and mitochondrial function. Highlights: Cobalt chloride exposure affected ovary coefficient and follicular growth. Cobalt chloride exposure decreased the occurrence rate of germ vesicle breakdown and polar body extrusion in mouse oocytes. Cobalt chloride exposure disorganized meiotic spindle formation and disturbed chromosome alignment in mouse oocytes. Cobalt chloride exposure disturbed actin reorganization and spindle location in mouse oocytes. Cobalt chloride exposure resulted in abnormal mitochondrial morphology and function in mouse oocytes.